2022
DOI: 10.14218/jcth.2021.00460
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Dubin-Johnson Syndrome and its Differentiation from Biliary Atresia

Abstract: Background and Aims:The aim was to determine if liver biochemistry indices can be used as biomarkers to help differentiate patients with neonatal Dubin-Johnson syndrome (nDJS) from those with biliary atresia (BA). Methods: Patients with genetically-confirmed nDJS or cholangiographically confirmed BA were retrospectively enrolled and randomly assigned to discovery or verification cohorts. Their liver chemistries, measured during the neonatal period, were compared. Predictive values were calculated by receiver o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…The important caveat is that success or prognosis of the Kasai procedure is negatively impacted by increased age at time of surgery, therefore a timely referral is crucial. 4,6 In this issue of the journal, Liu et al 7 investigate how to make the distinction between BA and nDJS using simple hepatic function tests, which is a noble effort to achieve timely and cost-effective care. The difficulty arises because there can be an overlap in the clinical presentation of both conditions, especially when all of the liver function tests are abnormal in nDJS.…”
Section: Jcth20220023smentioning
confidence: 99%
See 2 more Smart Citations
“…The important caveat is that success or prognosis of the Kasai procedure is negatively impacted by increased age at time of surgery, therefore a timely referral is crucial. 4,6 In this issue of the journal, Liu et al 7 investigate how to make the distinction between BA and nDJS using simple hepatic function tests, which is a noble effort to achieve timely and cost-effective care. The difficulty arises because there can be an overlap in the clinical presentation of both conditions, especially when all of the liver function tests are abnormal in nDJS.…”
Section: Jcth20220023smentioning
confidence: 99%
“…A hepatobiliary iminodiacetic acid scan can exclude BA when there is excretion into the small bowel, but is often noncontributory. 4 Liu et al 7 found that overall liver chemistries are lower in nDBS compared with BA. Using specific cutoffs for liver tests, they found that an AST level of <87 IU/L had a high sensitivity and specificity for nDBS, and therefore highlight its potential as a sensitive biomarker to differentiate nDBS from BA.…”
Section: Jcth20220023smentioning
confidence: 99%
See 1 more Smart Citation
“…[8,9] Early and precise diagnosis not only streamlines clinical management but also avoids potential complications arising from misdiagnosis with other hepatic conditions. [10,11] This study presents a neonatal clinical perspective of the disease. Through this exploration, we may contribute to a better understanding of DJS' infancy presentation and its developmental trajectory.…”
Section: Introductionmentioning
confidence: 99%